PERAN MENDONGENG DALAM MELATIH KECERDASAN EMOSI ANAK USIA DINI - Niken Widiastuti (Fakultas Psikologi Universitas Tarumanagara, 2016)
Early childhood is a time that is most appropriate in developing the physical aspect-motor, cognitive, social-emotional, language, morality and religion. And one of the appropriate media to convey and train the child's emotional intelligence is the storytelling, and the family has a central role to determine the success of the child's achievements in managing emotions. Because fairy tales can help children cope with life by training patterns of thought and experience they interact with the environment (Benediktsdóttir, 2014). Through fairy tales help children not to be afraid of change and to be independent. The subject in this study is four mothers who always interact with their children. Within families that the basics of child development are formed, and in this case the parent is the key factor. In this connection, it is necessary to systematically and strategically efforts to develop and train the emotional intelligence of children through fairy tales.Keywords: Fairy tales, emotional intelligence, early child